Aging effect on microstructure and property of strontium zirconate coating co‐doped with double rare‐earth oxides. Issue 4 (17th September 2018) - Ma, Wen; Meng, Xiangfeng; Wen, Jing; Li, Enbo; Bai, Yu; Chen, Weidong; Dong, Hongying
Abstract: Strontium zirconate coating co‐doped with ytterbia and gadolinia (Sr(Zr0.9 Yb0.05 Gd0.05 )O2.95, SZYG) and strontium zirconate coating (SrZrO3, SZ) were prepared by atmospheric plasma spraying. The SZYG coating shows improved phase stability from room temperature to 1400°C, while its thermal conductivity ( 0.8 W m −1 K −1 ) is at least 40% lower than that of the SZ coating. Both SZYG and SZ coatings were heat‐treated at 1400°C up to 360 hours in air. The X‐ray diffraction results reveal that both the as‐sprayed SZYG and SZ coatings are composed of main phase SrZrO3 and secondary phase t ‐ZrO2 . These two phases do not undergo phase transition upon heat treatment up to 360 hours in the SZYG coating, whereas t ‐ZrO2 transforms into m ‐ZrO2 almost completely after 20 hours heat treatment in the SZ coating, suggesting a strong promoting role in stabilizing t ‐ZrO2 by the additions of Yb2 O3 and Gd2 O3 in the SZYG coating. The content of t ‐ZrO2 is 4.3 wt.% in the as‐sprayed SZYG coating and increases to 19.5 wt.% after 360 hours heat treatment, analyzed using Jade software. The thermal expansion coefficients (TECs) of the SZYG coatings have no abrupt decrease after heat treatment for more than 5 hours, whereas an abrupt decrease in the TECs of the SZ coating is observed after 100 hours heat treatment. The superior performance of the SZYG coating is attributed to the very stable secondary phase t ‐ZrO2 stabilized by the co‐doping of ytterbia and gadolinia.